Engineering p-n junctions and bandgap tuning of InSe nanolayers by controlled oxidation - Balakrishnan, Nilanthy; Kudrynskyi, Zakhar R.; Smith, Emily F.; Fay, Michael W.; Makarovsky, Oleg; Kovalyuk, Zakhar D.; Eaves, Laurence; Beton, Peter H.; Patanè, Amalia (IOP Publishing, 2017)
Exploitation of two-dimensional (2D) van der Waals (vdW) crystals can be hindered by the deterioration of the crystal surface over time due to oxidation. On the other hand, the existence of a stable oxide at room temperature can offer prospects for several applications. Here we report on the chemical reactivity of γ-InSe, a recent addition to the family of 2D vdW crystals. We demonstrate that, unlike other 2D materials, InSe nanolayers can be chemically stable under ambient conditions. However, both thermal- and photo-annealing in air induces the oxidation of the InSe surface, which converts a few surface layers of InSe into In2O3, thus forming an InSe/In2O3 heterostructure with distinct and interesting electronic properties. The oxidation can be activated in selected areas of the flake by laser writing or prevented by capping the InSe surface with an exfoliated flake of hexagonal boron nitride. We exploit the controlled oxidation of p-InSe to fabricate p-InSe/n-In2O3 junction diodes with room temperature electroluminescence and spectral response from the near-infrared to the visible and near-ultraviolet ranges. These findings reveal the limits and potential of thermal- and photo-oxidation of InSe in future technologies.